2020
DOI: 10.5334/sta.766
|View full text |Cite
|
Sign up to set email alerts
|

‘They Were Going to the Beach, Acting like Tourists, Drinking, Chasing Girls’: A Mixed-Methods Study on Community Perceptions of Sexual Exploitation and Abuse by UN Peacekeepers in Haiti

Abstract: The United Nations Stabilization Mission in Haiti (MINUSTAH) has been marred by reports of sexual exploitation and abuse (SEA) perpetrated against local women/girls. However, there is very limited empirical evidence on the community's perceptions regarding these sexual interactions. Through a mixed-methods approach, this article examines community experiences and perceptions of SEA, with three prominent themes arising: peacekeepers as tourists, peacekeepers as sexual exploiters and abusers, and peacekeepers as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…The 18 in-depth interviews on which the analysis is based were conducted between October and December 2017 with women in Haiti who were raising peacekeeper-fathered children. This qualitative research followed a larger mixed-methods study conducted from June to August 2017 (King et al, 2020;Lee and Bartels, 2020;Vahedi et al, 2021aVahedi et al, , 2021b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18 in-depth interviews on which the analysis is based were conducted between October and December 2017 with women in Haiti who were raising peacekeeper-fathered children. This qualitative research followed a larger mixed-methods study conducted from June to August 2017 (King et al, 2020;Lee and Bartels, 2020;Vahedi et al, 2021aVahedi et al, , 2021b.…”
Section: Methodsmentioning
confidence: 99%
“…The survival and material needs of Haitian women and girls are risk factors for transactional sex with peacekeepers (Vahedi et al, 2019;King et al, 2020). The greatest risk of conceiving a peacekeeper-fathered child lies at the intersection of power imbalances rooted in an adverse socio-economic context and adolescent girls' lower sexual agency with respect to accessing j JOURNAL OF AGGRESSION, CONFLICT AND PEACE RESEARCH j sexual/reproductive health services/information.…”
Section: Micro Level: Targeting Personal Knowledge Experiences Attitudes and Beliefsmentioning
confidence: 99%
“…The original study was designed to examine local perceptions about interactions between MINUSTAH personnel and local women and girls. Separately published analyses from the same dataset have focused on sexual exploitation and abuse (SEA) by MINUSTAH personnel (37) as well as peacekeeper-fathered children in…”
Section: Methodsmentioning
confidence: 99%
“…(45,46) Recent empirical research has highlighted this sexual exploitation and abuse and shed light on children born as a result. (37,38,47) Finally, it is important to note that over the years, several humanitarian and foreign aid debacles have been documented in Haiti, both pre-earthquake (48) and post-earthquake.…”
Section: Legacy Of Colonialismmentioning
confidence: 99%
“…Peacekeepers have been tied to cases of rape in the Central African Republic (HRW, 2016) and in South Sudan (The Guardian, 2018). Studies have also found evidence of vast sexual exploitation in Haiti , King et. al.…”
Section: Theoretical Frameworkmentioning
confidence: 98%